(untitled) (Journal of Plant Disease Sciences, 2020)
An experiment was initiated to study the efficacy of different standard and new fungicides against powdery mildew and anthracnose disease of mango at Regional Fruit Research Station, Vengurle, Maharashtra, India during 2017-18 and 2018-19 with eight treatments. Among the different treatments, newer molecule Pydiflumetofen 7.5% + difenoconazole 12.5% w/v (200 SC) @ 0.6 ml/L of water recorded significantly lower per cent disease index of anthracnose (6.53%) which resulted 83.78 per cent reduction in per cent disease index over control (40.27%). In respect of powdery mildew, significantly minimum per cent (8.88) disease index and highest per cent disease control (82.88) recorded in treatment T4 where Pydiflumetofen 7.5% + difenoconazole 12.5% w/v (200 SC) @ 0.6 ml/L of water applied as foliar spray.